Impacts of predator–prey interaction on managing maximum sustainable yield and resilience - Pujaru, Kanisha; Kar, Tapan Kumar (Nonlinear Analysis: Modelling and Control, 2020)
This paper gives a broad outline of some comparative analysis of two ecological services, namely, yield and resilience of a generalist predator–prey system. Although either prey or predator species can be harvested at maximum sustainable yield (MSY) level, yet there is a trade-off between yield and resilience. When both the species are harvested simultaneously, MSY increase by changing catchabilities always increases the system resilience both in prey- and predator-oriented fishery. In particular, a prey-oriented fishery with low prey catchability gives more yield and resilience but in case of predator-oriented fishery with high predator catchability, gives more of these ecological services. Thus to get both the optimum yield and resilience, a balanced harvesting approach is needed between the prey and predator trophic levels. Throughout the analysis, we use both the analytical as well as numerical techniques.